Neural Network for Recognition of County Centre Post Codes - Gold, Hrvoje; Samodol, Mario (Promet - Traffic&Transportation, 2002)
The work represents an artificial neural networkf01· recognitionof county centre post codes. The neural networkPOSTKLAS se1ves as the classification system for the sorting oftwo-digit address data. The de1·eloped model represents atwo-layer network which learns by using backpropagation algorithm.The method of address data recording in the model hasbeen presented. By analysing the sorting results the possibilitywas determined of applying the developed neural network forrecognition even in cases of distorted input pal/erns. The modellingwas done by means of Mat/ab programming ~ystem.